Framework for developing a national surgical, obstetric and anaesthesia plan. Issue 5 (24th July 2019) - Sonderman, K A; Citron, I; Mukhopadhyay, S; Albutt, K; Taylor, K; Jumbam, D; Iverson, K R; Nthele, M; Bekele, A; Rwamasirabo, E; Maongezi, S; Steer, M L; et al.
Abstract: Background: Emergency and essential surgical, obstetric and anaesthesia (SOA) care are now recognized components of universal health coverage, necessary for a functional health system. To improve surgical care at a national level, strategic planning addressing the six domains of a surgical system is needed. This paper details a process for development of a national surgical, obstetric and anaesthesia plan (NSOAP) based on the experiences of frontline providers, Ministry of Health officials, WHO leaders, and consultants. Methods: Development of a NSOAP involves eight key steps: Ministry support and ownership; situation analysis and baseline assessments; stakeholder engagement and priority setting; drafting and validation; monitoring and evaluation; costing; governance; and implementation. Drafting a NSOAP involves defining the current gaps in care, synthesizing and prioritizing solutions, and providing an implementation and monitoring plan with a projected cost for the six domains of a surgical system: infrastructure, service delivery, workforce, information management, finance and governance. Results: To date, four countries have completed NSOAPs and 23 more have committed to development. Lessons learned from these previous NSOAP processes are described in detail. Conclusion: There is global movement to address the burden of surgical disease, improving quality and access to SOA care. The development of a strategic plan to address gaps across the SOA system systematically is a critical first step to ensuring countrywide scale-up of surgical system-strengthening activities. Graphical Abstract: This article describes a possible skeleton process for developing a national surgical, obstetric and anaesthesia plan (NSOAP) from the authors' experiences of developing some of the world's first NSOAPs in low- and middle-income countries. It discusses the specific challenges encountered and highlights lessons learned from navigating this process. Reproducible framework for improving global surgical care